Good practice report : nurturing graduate employability in higher education. - Kinash, Shelley; Crane, Linda; Judd, Madelaine-Marie (Australia. Office for Learning and Teaching, 2016)
This good practice report is concerned with graduate employability in Australian higher education. The authors: collected reports and analysed themes, disciplines, aims, outcomes and impact of Australian Government Office for Learning and Teaching (OLT) Promotion of Excellence in Learning and Teaching in Higher Education (PELTHE) graduate employability initiatives with final reports published between 2010 and 2015; invited descriptions of Wharton-QS Stars Reimagine Education 2015 shortlisted international awardees for nurturing employability, and described and analysed themes, disciplines and impact of these innovations; and Identified the overall trends in graduate employability research and innovation and made recommendations for future work on this domain.